Relationship between some motoric and technical performance characteristics of U17 Turkish national badminton players - Özgür, B.; Hotaman, F. (Journal of Physical Education and Sport, 2020)
This study investigates the relationship between some motoric and technical performance characteristics of U17 Turkish national badminton players. The participants of the study are five males, median age of 15 with seven years of training history, and nine females, median age of 15.5 years with six and a half years of sports experience. Participants' height, body weight, BMI, 20m speed, 20 m reaction speed, 20 m backward speed, quickness, standing long jump, vertical jump, flexibility, medicine ball throwing, hand-grip strength, back strength, leg strength and aerobic power have all been tested. Short serve, high serve, clear, drop shot and smash tests have been used to determine technical performance components. The total points (TP) in the technical tests have also been calculated. The relationship between the motoric and technical performance values of the participants has been evaluated by Spearman Correlation analysis. In males, significant relationships have been observed between high service with BMI and TP, 20 m speed with clear and TP, standing long jump with drop shot and smash, vertical jump with clear and TP, hand-grip strength and TP (p<0.05). In females, significant relationships have been found between medicine ball throwing with clear and TP, hand-grip strength with clear and TP, back strength with clear and TP, leg strength with clear and drop shot, aerobic power and drop shot (p<0.05). It has been observed that technical performance increased with the development of speed-power qualities in males and with the increase in strength in females. Therefore, while planning the physical preparation program for athletes of this age group, in addition to general studies, it is recommended to focus more on speed and explosive power for males, and strength training for females.